Образ жінки в творчості Хайріла Анвара в період воєнних років - Косенко Шахіде Юріївна (My University, 2024)
Робота присвячена аналізу однієї з ключових тем у творчості класика індонезійської та світової літератури поета Хайріла Анвара, - образу жінки у його віршах, написаних впродовж 1945 – 1949 років. Новизна роботи полягає в тому, що у ній здійснюється спроба глибинного розуміння творчості найвідомішого індонезійського літератора, вірші якого перекладені багатьма мовами світу, а сама творчість є вкрай важливою для правильного розуміння сучасного стану індонезійської літератури й культури, зважаючи на колосальний вплив Хайріла Анвара на розвиток індонезійської літературної мови й поезії цією мовою. Також, задля кращого розуміння проблематики, котра вивчається, було вперше здійснено переклади кількох важливих творів Хайріла Анвара, які наводяться в додатках до цієї роботи.

The work is devoted to the analysis of one of the key themes in the work of the classics of Indonesian and world literature by the poet Chairil Anwar, - the image of a woman in his poems written during 1945-1949. The novelty of the work is because it is an attempt at a deep understanding of creativity the most famous Indonesian writer, whose poems have been translated by many languages of the world, and creativity itself is extremely important for correct understanding the current state of Indonesian literature and culture, taking into account the colossal influence of Сhairil Anwar on the development of Indonesian literature speech and poetry in this language. Also, for a better understanding of the problem, which is being studied, several important works were translated for the first time Chairil Anwar, which are given in the appendices to this work. In accordance with the purpose of this study, the main methods in this work there was a method of theoretical analysis, a descriptive method and a method of psychoanalysis.
The image of a woman in the works of Chairil Anwar during the war years
Keywords: Хайріл Анвар; індонезійська поезія; війна за незалежність Індонезії 1945-1949; Іда